Land Suitability Index for Estimating Sugar Cane Productivity in the Humid Tropics of South Sulawesi Indonesia - Risma Neswati; Christianto Lopulisa; Muhammad Nathan; Andi Ramlan (UNIVERSITY OF LAMPUNG, 2016)
This research was completed using mixed qualitative and quantitative methods. Field surveys were executed in sugar cane plantation throughout South Sulawesi Indonesia. Land suitability analyses were performed using a parametric approach with Storie’s index equation followed up with correlation analysis using the Pearson correlation. Results revealed that the period for sugarcane crop growth in the humid tropic relatively dry regions of South Sulawesi Indonesia lasted for the months of November to July. The land suitability for sugar cane in the research location was moderately suitable (S2c) and marginally suitable (S3c, S3s, S3s,f and S3c,w) with limiting factors such as relative humidity during crop maturation phase, the duration of sunlight, soil depth, soil texture, soil pH and soil drainage. Land suitability index at the research location ranged from 25.2 to 55.0; sugar cane yields ranged from 30.3 to 62.0 Mg ha-1 year-1. Pearson correlation coefficient (r) between LSI with cane and sugar productivity were 0.81 and 0.84 respectively, signifying the strength of the correlation between the two values. This also indicates that land suitability index can be estimating the potential crop yield in the humid tropicsthat relatively dry climate regions.